Pengaruh Terapi Murottal Surah Ar-Rahman terhadap Tingkat Dismenore pada Remaja - Rahmayanti, Delvi; Taqiyah, Yusrah; Alam, Rizqy Iftitah (Window of Nursing Journal, 2021)
Dysmenorrhea is pain before or during menstruation which can be primary or secondary due to an increase in the hormone prostaglandin which causes the uterine muscles to contract. The incidence of dysmenorrhea in the world is quite large, on average more than 50% of women in every country experience menstrual pain. This study aims to determine the effect of murottal surah ar-rahman therapy on the level of dysmenorrhea in adolescents in SMA Negeri 6 Kota Bau-Bau in 2020. The type of research used is quantitative experiment with Quasi Experimental design, pre-post test experimental group and control group using purposive sampling technique. With a sample size of 20 respondents in the intervention group and 20 respondents in the control group. The relationship test was carried out with the Paired Sample T-test with a significance level of <0.05. The results showed that there was an effect between murottal surah ar-rahman therapy on the level of dysmenorrhea with a value of p = 0.000, where the value of p <a, then Ha was accepted. The conclusion of this study is that before being given murottal surah ar-rahman therapy in adolescents, they experienced a controlled moderate and severe pain scale, after being given murottal surah ar-rahman therapy the adolescents experienced a decrease in pain levels from moderate pain, mild pain, to no pain. And there is an effect between murottal sura ar- rahman therapy on the level of dysmenorrhea in adolescents in SMA Negeri 6 Kota Bau-Bau.